TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy and preparation method thereof

By doping Cu or Sr in TiZrNb-based alloy and adopting reasonable alloy composition design and heat treatment technology, the problem of insufficient performance of traditional alloys in high-temperature environments is solved, and the coordinated optimization of the strength, antibacteriality, toughness and heat impact resistance of the material is achieved, which is suitable for applications in high-temperature environments.

CN119843090AActive Publication Date: 2025-04-18SHANDONG MACHINERY DESIGN INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510031292.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Traditional alloys face the problems of cracking tendency under thermal shock, difficulty in taking into account the strength and toughness balance and poor processing adaptability in high temperature environments. In addition, the concentration of thermal stress in Ti-Zr-Nb alloys leads to the generation and expansion of material microcracks under rapid cooling conditions, which increases the risk of service life. At the same time, its antibacterial properties are insufficient, and there is a potential risk of infection.

Method used

By doping Cu or Sr in TiZrNb-based alloys, the alloy composition and heat treatment process are designed to achieve synergistic optimization of the strength, antibacteriality, toughness and heat impact resistance of the material. The specific steps include using the intermediate alloys TiZr, TiNb and TiM as raw materials, melting using an intermediate frequency induction furnace, and performing process treatments such as wire cutting, solid solution treatment, water quenching and electrical pulse annealing.

Benefits of technology

The high strength, excellent antibacterial properties and thermal shock resistance of TiZrNbCu or TiZrNbSr alloy are achieved, effectively reducing material cracks and failures caused by thermal stress, reducing infection risk, and improving the biocompatibility and applicability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843090A_ABST
    Figure CN119843090A_ABST
Patent Text Reader

Abstract

The invention discloses a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy and a preparation method thereof, and relates to the technical field of medium-entropy alloys, the chemical formula is TixZryNbzMh, M is Cu or Sr, x, y, z and h are molar percentages of chemical elements Ti, Zr, Nb and M respectively, x = y = z is more than 0 and less than or equal to 35, h is more than 3 and less than or equal to 10, when M is Cu, the antibacterial rate reaches 50%-60%, the alloy has high strength and thermal shock resistance, when M is Sr, the antibacterial rate reaches 30%-50%, and when M is Sr, the antibacterial rate reaches 30%-50%. The TiZrNbCu alloy or the TiZrNbSr alloy has high strength and heat shock resistance, the TiZrNbCu alloy or the TiZrNbSr alloy shows excellent heat shock resistance after being subjected to electric pulse annealing at 500 DEG C, and material cracks and failures caused by thermal stress can be effectively reduced. The excellent thermal shock resistance of the alloy is benefited from the unique microstructure and excellent thermal stability of the alloy, so that the alloy can be widely applied to the field with higher thermal shock resistance requirements in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy alloys, and in particular relates to a TiZrNb-based Cu or Sr-doped antibacterial implantable medium entropy alloy and a preparation method thereof. Background Art

[0002] Medium-entropy alloys are between traditional alloys and high-entropy alloys. They inherit the excellent properties of high-entropy alloys, and because of the small number of main elements, the mixed entropy is close to that of traditional alloys, which has better potential for industrial application. However, the application of traditional alloys under extreme conditions, especially in high-temperature environments, still faces many challenges, such as cracking tendency under thermal shock or difficulty in balancing strength and toughness, as well as poor processing adaptability.

[0003] TiZrNb alloy has become a research hotspot due to its light weight or high strength and excellent high temperature resistance. Ti, Zr and Nb are elements with high melting points and good oxidation resistance. The alloys composed of them show remarkable stability in high temperature environments. However, although Ti-Zr-Nb shows good performance in the high temperature field, its thermal shock resistance and comprehensive mechanical properties still have room for improvement. Especially under rapid temperature rise and fall conditions, thermal stress concentration can easily lead to the generation and expansion of microcracks in the material, thereby reducing the service life. In order to address these problems, researchers have proposed doping alloying elements in the Ti-Zr-Nb system to further optimize the material properties. The entropy alloy in TiZrNb itself does not have the characteristics of sterilization and disinfection, which may lead to potential infection risks in biomedical applications.

[0004] At present, the research on this system alloy is mainly concentrated in the laboratory stage, and its industrial preparation, process optimization and long-term service performance stability are still technical bottlenecks that need to be broken through. In view of the problems in the above technical background, the present invention proposes a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy and a preparation method thereof. By rationally designing the alloy composition and heat treatment process, the present invention realizes the synergistic optimization of material strength, antibacterial properties, toughness and thermal shock resistance in a low-density system, providing new research ideas and technical approaches for the practical application of medium-entropy alloys. Summary of the invention

[0005] The object of the present invention is to provide a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy and a preparation method thereof, so as to solve the problems raised by the above-mentioned background technology.

[0006] To solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] The present invention discloses a method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy, comprising: xZr y Nb z M, where M is Cu or Sr, x, y, z, and h are the molar percentages of chemical elements Ti, Zr, Nb, and M respectively, 0 < x = y = z ≤ 35, 3 < h ≤ 10. When M is Cu, the antibacterial rate reaches 50% - 60%, and it has high strength and heat shock resistance. When M is Sr, the antibacterial rate reaches 30% - 50%, and it has high strength and heat shock resistance. The manufacturing steps are as follows: Step 1: Use intermediate alloys TiZr, TiNb, and TiM as raw materials and melt them in an intermediate frequency induction furnace;

[0008] Step 2: Cut the medium entropy alloy ingot into thin slices by wire cutting;

[0009] Step 3: Put the thin slices into a box-type muffle furnace for solution treatment, and then put them into water for water quenching after the solution treatment;

[0010] Step 4: Take the medium entropy alloy material obtained in Step 3 for annealing treatment under electric pulse conditions, and then cool it to finally obtain an implantable medium entropy alloy material with high strength, excellent antibacterial performance, and heat shock resistance.

[0011] Furthermore, calculate the equimolar ratio of Ti, Zr, and Nb in the alloy according to M. The molar percentage of M is 3% < h ≤ 10%, and the molar percentages of Ti, Zr, and Nb are obtained through calculation Then calculate the contents of the three intermediate alloys TiZr, TiNb, and TiM according to the following equations: f TiZr ·TiZr Ti +f TiNb ·TiNb Ti +f TiM ·TiM Ti = x; f TiZr ·TiZr Zr = x; f TiNb ·TiNb Nb = x; f TiM ·TiM M = h; f TiZr +f TiNb +f TiM = 1; f TiZr 、f TiNb 、f TiM are the mass percentages required for the intermediate alloys TiZr, TiNb, and TiM during the melting process respectively; TiZr Ti 、TiZr Zr 、TiNb Ti 、TiNb Nb 、TiM M、 TiM Ti are the composition percentages of each intermediate alloy.​​

[0012] Furthermore, the power of the medium frequency induction furnace is 50-100kW. During the smelting process, the induction furnace needs to be preheated to 500-600°C, and then gradually heated up in a no-load state at a heating rate of 10°C / min to 1400°C. The three raw materials of TiZr, TiM and TiNb are gradually put into the medium frequency induction furnace. The frequency of the medium frequency induction furnace is set between 500Hz and 5kHz. A baffle is used at the furnace mouth. The baffle is used for heat insulation, oxidation prevention, pollution prevention and safety protection to ensure the smooth progress of the smelting process and improve the final alloy quality. After the smelting is completed, the alloy liquid is poured into the preheated mold, and the mold temperature is maintained between 300-500°C. After the alloy liquid in the mold is cooled to room temperature, the final TiZrNbM medium entropy alloy is obtained.

[0013] Furthermore, the thickness of the slice cut at the center line is 2 mm.

[0014] Furthermore, the solution treatment temperature is 1000° C., and the solution treatment time is 1 hour.

[0015] Furthermore, the electric pulse heating frequency is 1-10 kHz and the pulse width is 10-500 microseconds, which ensures that the alloy temperature rises evenly and avoids overheating.

[0016] Furthermore, the pulse current intensity is 30-100A, ensuring sufficient heating effect without damaging the alloy.

[0017] Furthermore, the annealing process is maintained for 1 hour, and uniform heating of the alloy promotes homogenization of grains and stress release.

[0018] Furthermore, a medium-entropy alloy was prepared using the above-mentioned TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy preparation method.

[0019] The present invention has the following beneficial effects:

[0020] 1. TiZrNbCu alloy exhibits excellent thermal shock resistance after 500℃ electric pulse annealing, which can effectively reduce material cracks and failures caused by thermal stress. Its excellent thermal shock resistance is due to the unique microstructure and excellent thermal stability of the alloy, and can be widely used in fields with high requirements for thermal shock resistance in high temperature environments.

[0021] 2. TiZrNb-based Cu-doped medium-entropy alloys have significant antibacterial properties, showing high inhibitory effects on common bacteria such as Staphylococcus aureus. This performance is due to the uniform distribution of Cu and the continuous release of antibacterial ions, combined with the biocompatibility of the alloy, making it an ideal material for implantable medical devices, effectively reducing the risk of infection and improving the safety and reliability of implants.

[0022] 3. After 500℃ electric pulse annealing, TiZrNbSr alloy shows excellent thermal shock resistance, effectively reducing cracks and failures caused by thermal stress. It enhances thermal stability and thermal fatigue resistance. The alloy shows strong oxidation resistance and good thermal expansion matching at high temperature, and is suitable for applications with high requirements for thermal shock resistance in high temperature environments.

[0023] 4. TiZrNb-based Sr-doped medium-entropy alloys have significant antibacterial properties and can effectively inhibit the growth of common bacteria, such as Staphylococcus aureus and Escherichia coli. The incorporation of Sr improves the surface properties of the alloy and may inhibit bacterial attachment and reproduction by releasing antibacterial ions. Combined with the corrosion resistance of TiZrNb alloys themselves, these alloys have broad application potential in medical devices, environmental protection and other fields.

[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0026] Figure 1-1 The annealed XRD patterns of TiZrNbCu alloy, TiZrNbSr alloy and TiZrNb alloy.

[0027] Figure 1-2 This is the XRD pattern of the annealed TiZrNbSr alloy.

[0028] Figure 2 This is a picture of TiZrNb alloy sample.

[0029] Figure 3 This is a picture of the TiZrNb alloy sample annealed at 500℃.

[0030] Figure 4-1 This is a picture of the TiZrNbCu alloy sample annealed at 500℃.

[0031] Figure 4-2 This is a picture of the TiZrNbSr alloy sample annealed at 500℃.

[0032] Figure 5 This is the 500℃ hardness diagram of TiZrNbCu alloy, TiZrNbSr alloy and TiZrNb alloy.

[0033] Figure 6Hardness diagram of TiZrNbCu alloy, TiZrNbSr alloy and TiZrNb alloy at different rolling rates.

[0034] Figure 7 These are stress-strain diagrams for TiZrNbCu alloy, TiZrNbSr alloy and TiZrNb alloy at 70% rolling rate.

[0035] Figure 8-1 This is the metallographic diagram of TiZrNbCu alloy annealed at 500℃.

[0036] Figure 8-2 This is the metallographic phase diagram of TiZrNbSr alloy annealed at 500℃. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] See also Figure 1-1 to Figure 8-2 As shown, the present invention is a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy and a preparation method thereof, comprising a chemical formula of Ti x Zr y Nb z M h , M is Cu or Sr, x, y, z, h are the molar percentages of chemical elements Ti, Zr, Nb, and M respectively, 0<x=y=z≤35, 3<h≤10, when M is Cu, the antibacterial rate reaches 50%-60%, with high strength and heat shock resistance, when M is Sr, the antibacterial rate reaches 30%-50%, with high strength and heat shock resistance, and the production steps are as follows:

[0039] Step 1, using intermediate alloys TiZr, TiNb and TiM as raw materials and smelting them in a medium frequency induction furnace;

[0040] Step 2, obtaining thin slices by wire cutting the medium entropy alloy ingot;

[0041] Step 3, the slice is placed in a box-type muffle furnace for solution treatment, and after the solution treatment, it is placed in water for water quenching;

[0042] Step 4: Take the medium-entropy alloy material prepared in Step 3, perform annealing treatment under electro-pulse conditions, and then cool it to finally obtain an implantable medium-entropy alloy material with high strength, excellent antibacterial properties, and heat shock resistance. Doping Cu or Sr into the TiZrNb medium-entropy alloy reveals the alloy composition, achieving high uniformity and avoiding composition segregation. The combination of solution treatment and electro-pulse annealing endows the material with high strength, exhibits good thermal stability in high-temperature environments, and significantly improves the ability to resist thermal stress.

[0043] The equimolar ratios of Ti, Zr, and Nb in the alloy are calculated according to M, where the molar percentage of M is 3% < h ≤ 10%, and the molar percentages of Ti, Zr, and Nb are obtained through calculation. Then, calculate the contents of three intermediate alloys, namely TiZr, TiNb, and TiM, according to the following equations: f TiZr ·TiZr Ti + f TiNb ·TiNb Ti + f TiM ·TiM Ti = x; f TiZr ·TiZr Zr = x; f TiNb ·TiNb Nb = x; f TiM ·TiM M = h; f TiZr + f TiNb + f TiM = 1; f TiZr 、f TiNb 、f TiM are the mass percentages required for the intermediate alloys TiZr, TiNb, and TiM during the melting process; TiZr Ti 、TiZr Zr 、TiNb Ti 、TiNb Nb 、TiM M、 TiM Ti are the composition percentages of each intermediate alloy.

[0044] The power of the medium frequency induction furnace is 50-100kW. During the smelting process, the induction furnace needs to be preheated to 500-600°C, and then gradually heated up in a no-load state at a heating rate of 10°C / min to 1400°C. The three raw materials of TiZr, TiM and TiNb are gradually put into the medium frequency induction furnace. The frequency of the medium frequency induction furnace is set between 500Hz and 5kHz. A baffle is used at the furnace mouth. The baffle is used for heat insulation, oxidation prevention, pollution prevention and safety protection to ensure the smooth progress of the smelting process and improve the quality of the final alloy. After the smelting is completed, the alloy liquid is poured into the preheated mold, and the mold temperature is maintained between 300-500°C. After the alloy liquid in the mold is cooled to room temperature, the final TiZrNbM medium entropy alloy is obtained.

[0045] The thickness of the slice cut at the center line is 2 mm.

[0046] The solution treatment temperature is 1000° C., and the solution treatment time is 1 hour.

[0047] The electric pulse heating frequency is 1-10 kHz and the pulse width is 10-500 microseconds, which ensures that the alloy temperature rises evenly and avoids overheating.

[0048] The pulse current intensity is 30-100A, ensuring sufficient heating effect without damaging the alloy.

[0049] The annealing process is maintained for 1 hour, and the uniform heating of the alloy promotes the homogenization of the grains and the release of stress.

[0050] The medium-entropy alloy is prepared by using the above-mentioned TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy preparation method.

[0051] Example 1

[0052] A TiZrNb-based Cu-doped antibacterial implantable medium-entropy alloy is prepared by preparing a TiZrCu alloy, wherein the Cu content is 3%, 6%, 8% or 10%:

[0053] (1) High-purity TiZr, TiNb and TiCu are placed in a medium-frequency induction furnace as raw materials and melted by induction heating. After smelting, the alloy liquid is poured into a preheated mold. The temperature of the mold is generally maintained between 300-500°C. After the alloy liquid in the mold is cooled to room temperature, the final TiZrNbCu medium-entropy alloy is obtained.

[0054] (2) cutting the alloy ingot into thin sheets with a thickness of 2 mm using wire cutting;

[0055] (3) placing the slice in a box-type muffle furnace for solution treatment at a temperature of 1000°C for 1 hour, and immediately quenching with water after solution treatment;

[0056] (4) Annealing temperature under electric pulse condition is 500℃ and time is 1 hour.

[0057] The TiZrNbCu alloy prepared in Example 1 was subjected to XRD analysis, and the results were as follows: Figure 1-1 As shown. After annealing at 500℃, the samples of TiZrNb and TiZrNbCu alloys are shown Figure 3 and Figure 4-1 The annealed hardness and the hardness at different rolling rates are shown in Figure 5 and Figure 6 The stress-strain curve obtained by the tensile testing machine is shown in Figure 7 The metallographic image of TiZrNbCu alloy annealed at 500℃ is shown in Figure 8-1 shown.

[0058] Figure 1-1 The peak of TiZrNbCu in the sample has changed significantly compared with TiZrNb, especially in the range of 40° to 50°, indicating that the crystal structure has changed significantly after the addition of Cu. This shows that the introduction of Cu has contributed to the formation of the TiCu3 phase. The diffraction peak of TiZrNbCu is sharper, indicating that it has a higher degree of crystallinity or a more stable crystal structure, which helps to improve the performance of the material, such as mechanical strength. Figure 2 This is a sample of TiZrNb alloy after wire cutting. There is no crack on the surface of the sample before heat treatment. After annealing at 500℃, there are obvious cracks on the surface of TiZrNb alloy. Figure 3 As shown, there is no obvious crack after adding Cu. Figure 3 and Figure 4-1 The hardness of TiZrNb and TiZrNbCu alloys is shown in Figure 5 and Figure 6 As shown in Figure 2, the addition of Cu significantly improves the hardness, which is attributed to the solid solution strengthening effect and the fine grain structure formed during processing. At the same time, the higher cold working rate leads to an increase in dislocation density, which further enhances the hardness and strength of the material. Figure 7 As shown in the figure, the addition of Cu significantly improves the tensile strength and ductility of the alloy. At the same time, TiZrNbCu has stronger plastic deformation ability. These results indicate that the addition of Cu effectively enhances the strength and ductility of the alloy through solid solution strengthening and microstructure refinement effects.

[0059] In the present invention, other alloy components prepared by the same method as in Example 1 are shown in Table 1 below:

[0060] Table 1

[0061] element Ti Zr Nb Cu Ingredient one 32.3 32.3 32.3 3 Ingredient 2 31.3 31.3 31.3 6 Ingredients 3 30.7 30.7 30.7 8 Ingredients 4 30 30 30 10

[0062] The TiZrNbCu alloy of the present application exhibits excellent thermal shock resistance after 500°C electric pulse annealing, which can effectively reduce material cracks and failures caused by thermal stress. Its excellent thermal shock resistance is due to the unique microstructure and excellent thermal stability of the alloy, and can be widely used in fields with high requirements for thermal shock resistance in high temperature environments.

[0063] The TiZrNb-based Cu-doped medium-entropy alloy of the present application has significant antibacterial properties, and exhibits a highly effective inhibitory effect on common bacteria such as Staphylococcus aureus, etc. This performance is due to the uniform distribution of Cu and the continuous release of antibacterial ions, combined with the biocompatibility of the alloy, making it an ideal material for implantable medical devices, effectively reducing the risk of infection and improving the safety and reliability of implants.

[0064] The Cu element of the present application has excellent thermal conductivity and oxidation resistance. High thermal conductivity can significantly improve the thermal conductivity of the alloy, thereby effectively alleviating the temperature gradient under thermal shock conditions and the resulting thermal stress concentration, and Cu can refine the grains in the alloy, optimize the microstructure, and improve the strength and toughness matching of the alloy. At the same time, it helps to improve the plasticity of the alloy, so that it shows better adaptability during processing. The introduction of the Cu element can not only significantly improve the mechanical properties of the entropy alloy in TiZrNb, but also because it has good antibacterial properties, it can effectively inhibit the growth and reproduction of bacteria. The addition of Cu can form an antibacterial environment on the implant surface by releasing copper ions, thereby reducing the risk of infection and improving the safety of the implant. The introduction of Cu can also improve the processability and wear resistance of the alloy, making the entropy alloy in TiZrNb more advantageous during manufacturing and use.

[0065] Example 2

[0066] TiZrNb-based Sr-doped antibacterial implantable medium-entropy alloys are prepared to prepare TiZrNbSr alloys, when the Sr content is 3%, 6%, 8% or 10%;

[0067] (1) The TiZrNbSr alloy ingot melted in a medium frequency induction furnace is wire cut to obtain a 2 mm thick sheet;

[0068] (2) placing the slice in a box-type muffle furnace for solution treatment at a temperature of 1000°C for 1 hour, and immediately quenching with water after solution treatment;

[0069] (3) Annealing temperature under electric pulse condition is 500℃ and time is 1 hour.

[0070] The TiZrNbSr alloy prepared in Example 2 was subjected to XRD analysis, and the results were as follows: Figure 1-2 As shown. After annealing at 500℃, the samples of TiZrNb and TiZrNbSr alloys are shown Figure 3 and Figure 4-2 The annealed hardness and the hardness at different rolling rates are shown in Figure 5 and Figure 6 The stress-strain curve obtained by the tensile testing machine is shown in Figure 7 The metallographic image of TiZrNbSr alloy annealed at 500℃ is shown in Figure 8-2 shown.

[0071] Figure 1-2 The (110), (200), and (211) are typical diffraction peaks of the body-centered cubic (BCC) structure crystal plane, with the (110) crystal plane as the main orientation. The distribution of this peak indicates that the TiZrNbSr alloy may have a single BCC structure, and the introduction of Sr helps to stabilize the BCC structure. After annealing at 500℃, there are obvious cracks on the surface of the TiZrNb alloy, such as Figure 3 As shown in Figure 2, after adding Sr, there is no obvious crack. Figure 3 and Figure 4-2 The hardness of TiZrNb and TiZrNbSr alloys is shown in Figure 5 and Figure 6 As shown in the figure, the hardness of the TiZrNbSr alloy after annealing and different rolling rates is significantly higher than that of the TiZrNb alloy. At the same time, the addition of Sr improves the tensile strength and ductility of the alloy, and the plastic deformation ability of TiZrNbSr is stronger, as shown in the figure. Figure 7 shown.

[0072] In the present invention, other alloy components prepared by the same method as in Example 2 are shown in Table 2 below:

[0073] Table 2

[0074]

[0075]

[0076] The TiZrNbSr alloy of the present application exhibits excellent thermal shock resistance after 500°C electric pulse annealing, effectively reducing cracks and failures caused by thermal stress. It also enhances thermal stability and thermal fatigue resistance. The alloy exhibits strong oxidation resistance and good thermal expansion matching at high temperatures, and is suitable for applications with high requirements for thermal shock resistance in high temperature environments.

[0077] The TiZrNb-based Sr-doped medium-entropy alloy of the present application has significant antibacterial properties and can effectively inhibit the growth of common bacteria, such as Staphylococcus aureus and Escherichia coli. The incorporation of the Sr element improves the surface properties of the alloy and may inhibit bacterial attachment and reproduction by releasing antibacterial ions. Combined with the corrosion resistance of the TiZrNb alloy itself, these alloys have broad application potential in the fields of medical devices, environmental protection, etc.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy, characterized in that: Including chemical formula Ti x Zr y Nb z M h , M is Cu or Sr, x, y, z, h are the molar percentages of chemical elements Ti, Zr, Nb, and M respectively, 0<x=y=z≤35, 3<h≤10, when M is Cu, the antibacterial rate reaches 50%-60%, with high strength and heat shock resistance, when M is Sr, the antibacterial rate reaches 30%-50%, with high strength and heat shock resistance, and the production steps are as follows: Step 1, using intermediate alloys TiZr, TiNb and TiM as raw materials and smelting them in a medium frequency induction furnace; Step 2, obtaining thin slices by wire cutting the medium entropy alloy ingot; Step 3, the slice is placed in a box-type muffle furnace for solution treatment, and after the solution treatment, it is placed in water for water quenching; Step 4: Take the medium-entropy alloy material obtained in step 3 and perform annealing treatment under electric pulse conditions, and then cool it to finally obtain an implantable medium-entropy alloy material with high strength, excellent antibacterial properties and heat shock resistance.

2. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The equimolar ratios of Ti, Zr, and Nb in the alloy are calculated according to M, where the molar percentage of M is 3% < h ≤ 10%, and the molar percentages of Ti, Zr, and Nb are obtained through calculation. Then, the contents of three intermediate alloys, namely TiZr, TiNb, and TiM, are calculated according to the following equations: f TiZr ·TiZr Ti + f TiNb ·TiNb Ti + f TiM ·TiM Ti = x; f TiZr ·TiZr Zr = x; f TiNb ·TiNb Nb = x; f TiM ·TiM M = h; f TiZr + f TiNb + f TiM = 1; f TiZr 、f TiNb 、f TiM are the mass percentages required for the intermediate alloys TiZr, TiNb, and TiM during the smelting process; TiZr Ti 、TiZr Zr 、TiNb Ti 、TiNb Nb 、TiM M、 TiM Ti are the component percentages of each intermediate alloy.

3. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The power of the medium frequency induction furnace is 50-100kW. During the smelting process, the induction furnace needs to be preheated to 500-600°C, and then gradually heated up in a no-load state at a heating rate of 10°C / min to 1400°C. The three raw materials of TiZr, TiM and TiNb are gradually put into the medium frequency induction furnace. The frequency of the medium frequency induction furnace is set between 500Hz and 5kHz. A baffle is used at the furnace mouth. The baffle is used for heat insulation, oxidation prevention, pollution prevention and safety protection to ensure the smooth progress of the smelting process and improve the quality of the final alloy. After the smelting is completed, the alloy liquid is poured into the preheated mold, and the mold temperature is maintained between 300-500°C. After the alloy liquid in the mold is cooled to room temperature, the final TiZrNbM medium entropy alloy is obtained.

4. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The thickness of the slice cut at the center line is 2 mm.

5. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The solution treatment temperature is 1000° C., and the solution treatment time is 1 hour.

6. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The electric pulse heating frequency is 1-10 kHz and the pulse width is 10-500 microseconds, which ensures that the alloy temperature rises evenly and avoids overheating.

7. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The pulse current intensity is 30-100A, ensuring sufficient heating effect without damaging the alloy.

8. The method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to claim 1, characterized in that: The annealing process is maintained for 1 hour, and the uniform heating of the alloy promotes the homogenization of the grains and the release of stress.

9. A TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy, prepared by the method for preparing a TiZrNb-based Cu or Sr-doped antibacterial implantable medium-entropy alloy according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of antibacterial zirconium-titanium-niobium-copper biological material

    CN109136600A

  • Ti-Zr-Nb-Ta-Cu series high-entropy alloy, preparation method thereof and application of Ti-Zr-Nb-Ta-Cu series high-entropy alloy in medical antibacterial materials

    CN114875293A

  • Preparation method of biomedical Ti-Zr-Nb series medium-entropy alloy and large cast ingot

    CN114908262A

  • TiZrNb-based high-entropy alloy and preparation method thereof

    CN116043091A

  • Preparation method of TiZrNb series refractory multi-principal-element alloy with uniform equiaxed fine grain structure

    CN117721334A